Deep learning approach towards accurate state of charge estimation for lithium-ion batteries using self-supervised transformer model - Hannan M.A.; How D.N.T.; Lipu M.S.H.; Mansor M.; Ker P.J.; Dong Z.Y.; Sahari K.S.M.; Tiong S.K.; Muttaqi K.M.; Mahlia T.M.I.; Blaabjerg F. (Nature Research, 2023)
article; deep learning; environmental temperature; human